2006
DOI: 10.1111/j.1399-0004.2007.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Family system characteristics and psychological adjustment to cancer susceptibility genetic testing: a prospective study

Abstract: This study examined prospectively the contribution of family functioning, differentiation to parents, family communication and support from relatives to psychological distress in individuals undergoing genetic susceptibility testing for a known familial pathogenic BRCA1/2 or Hereditary nonpolyposis colorectal cancer-related mutation. Family functioning, differentiation to parents, hereditary cancer-related family communication and perceived support from relatives were assessed in 271 participants for genetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 39 publications
1
74
0
Order By: Relevance
“…129 Finally, providing partner support and facilitating family communication regarding hereditary cancer has been recommended, because studies have demonstrated that family members may also experience distress throughout the genetic testing process. [130][131][132] Mutation carriers are faced with difficult decisions about risk-reducing prophylactic surgeries. Providing support for these decisions may facilitate the process and decrease distress.…”
Section: Discussionmentioning
confidence: 99%
“…129 Finally, providing partner support and facilitating family communication regarding hereditary cancer has been recommended, because studies have demonstrated that family members may also experience distress throughout the genetic testing process. [130][131][132] Mutation carriers are faced with difficult decisions about risk-reducing prophylactic surgeries. Providing support for these decisions may facilitate the process and decrease distress.…”
Section: Discussionmentioning
confidence: 99%
“…Positive implications were more often described by carriers than non-carriers, which may reflect adaptation and coping [12,30]. A minority of the families reported a negative impact, including isolation and guilt [26].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, suboptimal communication, poor family relations and decisions to restrict disclosure of information may hamper information spread [9,11]. Family structure and function may not only influence how family members receive information, but also how knowledge about an increased risk is handled, decisions related to genetic testing and participation in surveillance [8,10,12]. With the aim to explore family perspectives, we interviewed 27 members of Lynch syndrome families with focus on how family members perceived that knowledge about hereditary cancer has affected the family.…”
Section: Introductionmentioning
confidence: 99%
“…In many medical contexts, high monitors have been found to fare better when provided with detailed, but reassuring, information about their situation [65][66][67][68][69][70][71][72][73][74][75]. The information presented to them should be ample and accurate but framed less negatively, in a manner that distances or cools it, so their sense of vulnerability and distress does not panic them [37].…”
Section: Discussionmentioning
confidence: 99%